2018
DOI: 10.1101/253013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Folding Pathway of an Ig Domain is Conserved On and Off the Ribosome

Abstract: Proteins that fold cotranslationally may do so in a restricted configurational space, due to the volume occupied by the ribosome. How does this environment, coupled with the close proximity of the ribosome, affect the folding pathway of a protein? Previous studies have shown that the cotranslational folding process for many proteins, including small, single domains, is directly affected by the ribosome. Here, we investigate the cotranslational folding of an all-b immunoglobulin domain, titin I27. Using an arre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 80 publications
6
39
0
Order By: Relevance
“…These contacts may stimulate interactions between the NC residues in such way that the NC may be compacted and may allow formation of transient secondary structural elements, particularly at longer. Interesting parallels can also be drawn from recent cryo-EM studies of RNCs of small folded domains on shorter linker lengths: both spectrin (linker length 32aa) (Nilsson et al, 2017) and the immunoglobulin-like protein, I27, (linker length 35aa) (Tian et al, 2018), showing a preference for the orientation shown in our state 3 structure, suggesting that common sites of contact on the ribosome of the newly formed globular state may exist during co-translational folding.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These contacts may stimulate interactions between the NC residues in such way that the NC may be compacted and may allow formation of transient secondary structural elements, particularly at longer. Interesting parallels can also be drawn from recent cryo-EM studies of RNCs of small folded domains on shorter linker lengths: both spectrin (linker length 32aa) (Nilsson et al, 2017) and the immunoglobulin-like protein, I27, (linker length 35aa) (Tian et al, 2018), showing a preference for the orientation shown in our state 3 structure, suggesting that common sites of contact on the ribosome of the newly formed globular state may exist during co-translational folding.…”
Section: Discussionmentioning
confidence: 56%
“…Nascent chains (NC) can begin to acquire secondary structural elements in a cotranslational manner during emergence via the ribosome exit tunnel within the large subunit of the ribosome (Netzer W. et al, 1997;Thommen et al, 2017). Studies by cryo-EM have shown NC folding within the exit tunnel is largely limited to formation of rudimentary secondary structure, predominantly a helices within different areas of the tunnel while b hairpins as well as the formation of small domains in the wider vestibule region of the tunnel (Kosolapov and Deutsch., 2009;Bhushan et al, 2011;Lu et al, 2011;Nilsson et al, 2015;Holtkamp et al, 2015;Nilsson et al, 2017;Su et al, 2017;Agirrerazabala et al, 2017;Tian et al, 2018). Nonetheless, the polypeptides with more complex tertiary structure fold close to and outside the tunnel, as found for spectrin -a three-helix bundle protein, and titin, an all beta-sheet immunoglobulin domain (Nilsson et al, 2017;Tian et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, as these studies noted, forced unfolding measured by molecular tweezers cannot capture the transient folding of a nascent chain during its synthesis (33), and hence what is measured in these experiments is the effect of close proximity of the ribosome surface, rather than co-translational folding. The very robust folding behavior of these wellcharacterized, reversible folding models may indeed lead to indistinguishable folding behavior during translation, a model supported by recent force-feedback folding measurements (71). However, the model proteins selected for these studies are smaller than >75% of proteins in the E. coli proteome (24), whereas all known examples of synonymous codon-derived alterations to co-translational folding are much larger (e.g., (1,9,10,72)).…”
Section: Discussionmentioning
confidence: 90%
“…In all FPA studies published to date, the quantitative relation between the calculated fFL values and the underlying pulling force acting on the nascent chain has remained undefined (although attempts have been made to derive it from simulations or other kinds of theoretical modeling 11,38 . Using the PURE translation system, Goldman et al 6 showed that the interactions between the SecM AP and the ribosome exit tunnel can be disrupted by a mechanical force applied through optical tweezers, and that the rate by which the translational stall induced by the SecM AP is released, kR, increases in step with the amount of force, F, applied to the nascent chain, in a way that can be approximated by the Bell model 41 for force-induced rupture:…”
Section: A Quantitative Relation Between Ffl and Pulling Forcementioning
confidence: 99%
“…The discovery 2,3 and engineering 4,5 of translational arrest peptides (APs) has provided us with a new tool to examine how proteins fold cotranslationally. To date, the folding of several small proteins and protein domains has been studied using the force-sensitive AP from the E. coli SecM protein with a method we have called Force-Profile Analysis (FPA) [6][7][8][9][10][11][12][13][14][15] . Recently, we demonstrated that FPA faithfully picks up cotranslational protein folding events observed by direct biophysical measurements 15 .…”
Section: Introductionmentioning
confidence: 99%